Dividend Policy Mediates the Impact of Financial Performance and Asset Structure on Firm Value - Rizky, Dimas (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
In the country's economic growth, the construction industry is an important contributor and is directly influenced by government policies, because the government can regulate the economy by carrying out public works construction during periods of stagnation. The purpose of this study is to analyze and provide empirical evidence of Dividend Policy mediating the influence of Asset Structure on Company Value. The research was conducted using quantitative descriptive research methods. The population used is 18 manufacturing companies in the construction and building sector listed on the Indonesia Stock Exchange. The samples used were 10 companies. The analytical tools used use regression model tests, classical assumption tests, hypothesis tests and path analysis. The results of the study can be concluded indirectly Asset Structure through Dividend Policy has a significant influence on Company Value.